Estudio del trebol subterraneo en Salamanca. I.-Clasificacion botanica y fechas de floracion - Cordero, S.A.=700 1 Crespo, M.C.
(Es, En)
ilus., 29 ref.
Keywords: TRIFOLIUM SUBTERRANEUM; FLORACION; ECOLOGIA; DESARROLLO BIOLOGICO; ESPAÑA; TREBOL